The Romanian Social Worker Facing Challenges and Meeting Economic Opportunities Provided by the European Union - Fitzek, Sebastian (Calitatea Vieții, 2014)
This article analyzes to what extent the classical role of the Romanian social worker has been modified in relation to the challenges and also to the opportunities provided by the European Union. As a State Member from 1st of January 2007, Romania has been obliged to authentically reform the old labour environment to a powerful and capable system closer to that in the western countries. An analysis is provided regarding the modification of the therapeutical function in the context in which the social worker has to adopt new strategies towards the traditional Romanian beneficiaries who haven’t changed.